HTML5 Canvas for developers - Geary, David M. 1957- (O'Reilly, 2013)
"Learn how to use the HTML5 Canvas element and related HTML5 capabilities such as video and animation. This three-hour video shows you how to make the most of Canvas by demonstrating the use of compelling applications, including drawing programs and image filters."--Resource description page.